Receptive Orientation Behavior by May Welland in Edith Wharton's The Age of Innocence Novel: an Existentialist Psychoanalysis Perspective - Santoso, Fachrunnisa, Dr. M. Thoyibi, M.S, Titis Setyabudi S.S., M.Hum (2015)
This research paper aims to know receptive orientation behavior of the May Welland in The Age of Innocence novel. The objective of the research is to analyze the novel by using an existentialist psychoanalysis theory. The type of this research is descriptive qualitative research because there is no calculating data in this research. The data sources of the research are (1)the primary data of the research is The Age of Innocence novel by Edith Wharton, (2)the secondary data of the research taken from any information related to the novel such as biography of author, literary books, journal, and references from internet related with the study. The method to analyze this data is descriptive analysis. The result of this analysis is that May Welland's character is dominant as the receptive orientation behavior. She has 12 aspects as the positive and negative aspect of the receptive orientation behavior by Fromm's theory.